2021
DOI: 10.1001/jamapediatrics.2021.2328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Detection of Clostridioides difficile Among Asymptomatic Children

Abstract: IMPORTANCE Detection of Clostridioides difficile has frequently been described in asymptomatic infants and children, but accurate estimates across the age spectrum are unavailable. OBJECTIVE To assess the prevalence of C difficile detection among asymptomatic children across the age spectrum. DATA SOURCES This systematic review and meta-analysis included a search of the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, CINAHL, Scopus, and Web of Science for articles published from January 1, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 131 publications
1
22
0
Order By: Relevance
“…Importantly, the cumulative effect of antimicrobial exposure on C. difficile colonization remained in vaginally-delivered infants, even after adjusting for covariates, showing that the vulnerability of full-term newborns to antibiotic exposure is not related to caesarean delivery. Consistent with what others have reported [ 15 ], we found that up to 31% of infants were colonized with C. difficile at a time when gut microbiota are being established. Antimicrobial exposure significantly increased C. difficile colonization at both 3–4 months of age and 12 months of age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, the cumulative effect of antimicrobial exposure on C. difficile colonization remained in vaginally-delivered infants, even after adjusting for covariates, showing that the vulnerability of full-term newborns to antibiotic exposure is not related to caesarean delivery. Consistent with what others have reported [ 15 ], we found that up to 31% of infants were colonized with C. difficile at a time when gut microbiota are being established. Antimicrobial exposure significantly increased C. difficile colonization at both 3–4 months of age and 12 months of age.…”
Section: Discussionsupporting
confidence: 92%
“…At the older infant age, the association with antimicrobials was strongest from perinatal (maternal IAP and newborn IV) antibiotic exposure (odds ratio (OR):1.33, 95% confidence interval (CI) 1.10–1.62; p = 0.003). Although C. difficile colonization of infants is asymptomatic [ 15 ], its presence in gut microbiota at this early age is associated with future asthma and allergic diseases [ 20 , 21 ]. Our study is the first to evaluate both the systemic antibiotic exposure and the environmental antimicrobial exposure of infants, with separate consideration of infants delivered vaginally and by caesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of these beneficial genera may participate in the immune response of opportunistic pathogens and the modulation of intestinal permeability. Besides, Helicobacter 29 , Peptoclostridium 30 and Aeromonas 31 were considered multifactorial and could lead to the immune host response in certain virulent circumstances. Although we couldn't clarify the precise role of the altered gut microbiota in ET due to its limitation to species level interpretation, we still confirmed its specific taxa difference and this published literature of such microbial function could give hints for further research.…”
Section: Discussionmentioning
confidence: 99%
“…If used, multiplex panels should be coupled with established diagnostic stewardship strategies ( 36 ), including annotation of pathogens not likely to benefit from antimicrobial treatment (e.g., STEC [ 12 , 37 ] and Salmonella [ 11 ]). In addition, selective suppression of results likely to indicate colonization (e.g., C. difficile in children <2 years old [ 38 , 39 ] and EPEC in high-income settings [ 40 , 41 ]) can prevent unnecessary treatment of these conditions. Suppression is ideally done at the instrument level to avoid putting laboratory personnel in the position of having information that is not made available to the clinical team.…”
Section: Discussionmentioning
confidence: 99%